Penerapan Pendekatan Sains Teknologi Masyarakat Pada Materi Daur Air Dalam Meningkatkan Hasil Belajar Siswa Di Kelas VI Sekolah Dasar - Amran, Muhammad (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2018)
This study used a qualitative approach and type of classroom action research. The problem formulation of this research is whether the application of Community Technology Science approach on the water cycle material can improve the learning outcomes of grade 6 students at SD Negeri139 Tea Musu? And how is the process of applying the Community Technology Science approach to the water cycle material in improving the learning outcomes of the 6th grade students of SD Negeri139 Tea Musu? The purpose of this research is to improve the learning outcomes of grade 6 students of SD Negeri139 Tea Musu on the water cycle material through the application of Science Community Technology approach, as well as to improve the process / activity of learning water cycle materials through the application of Science Technique VI class VI SD Negeri139 Tea Musu. The object of this research is the students of class VI SD Negeri139 Tea Musu. Data collection techniques used were teacher and student observation, and documentation. Based on the results of analysis and evaluation at the reflection stage, the results showed that, the application of Science Community Technology approaches effectively improve the process / activity and learning outcomes in the Water Recycle material in every cycle of action.